Intra- and postoperative relative angiotensin II deficiency in patients undergoing elective major abdominal surgery - Krenn, Katharina; Höbart, Petra; Adam, Lukas; Riemann, Gregor; Christiansen, Finn; Domenig, Oliver; Ullrich, Roman (Frontiers in Endocrinology, 2024)
Introduction The classical axis of the renin–angiotensin system (RAS) makes an important contribution to blood pressure regulation under general anesthesia via the vasopressor angiotensin II (Ang II). As part of the alternative RAS, angiotensin-converting enzyme 2 (ACE2) modulates the pro-inflammatory and fibrotic effects of Ang II by processing it into the organ-protective Ang 1–7, which is cleaved to Ang 1–5 by ACE. Although the levels of ACE2 may be associated with postoperative complications, alternative RAS metabolites have never been studied perioperatively. This study was designed to investigate the perioperative kinetics and balance of both RAS axes around major abdominal surgery. Methods In this observational cohort study, 35 patients undergoing elective major abdominal surgery were included. Blood sampling was performed before and after induction of anesthesia, at 1 h after skin incision, at the end of surgery, and on postoperative days (POD) 1, 3, and 7. The equilibrium concentrations of Ang I–IV, Ang 1–7, and Ang 1–5 in plasma were quantified using mass spectrometry. The plasma protein levels of ACE and ACE2 were measured with ELISA. Results Surgery caused a rapid, transient, and primarily renin-dependent activation of both RAS axes that returned to baseline on POD 1, followed by suppression. After induction, the Ang II/Ang I ratio persistently decreased, while the ACE levels started to increase on POD 1 (all p < 0.01 versus before anesthesia). Conversely, the ACE2 levels increased on POD 3 and 7 (both p < 0.001 versus before anesthesia), when the median Ang 1–7 concentrations were unquantifiably low. Discussion The postoperative elevation of ACE2 may prolong the decrease of the Ang II/Ang I ratio through the increased processing of Ang II. Further clarification of the intraoperative factors leading to relative Ang II deficiency and the sources of postoperatively elevated ACE2 is warranted.